Dimensionality of the Mental Toughness Questionnaire (MTQ48) - Perry, John L.; Strycharczyk, Doug; Dagnall, Neil; Denovan, Andrew; Papageorgiou, Kostas A.; Clough, Peter J. (Frontiers in Psychology, 2021)
Currently there is debate as to whether MT is a unidimensional or multidimensional construct To investigate dimensionality, we examined data from a sample of 78,947 participants, completed the mental toughness questionnaire-48 (MTQ48), a widely used measure of mental toughness. A series of exploratory structural equation models were tested to examine unidimensional, multidimensional, and bifactor solutions. Overall, the results show support for the multi-dimensional conceptualization of mental toughness, either as six independent but related factors, or as a bifactor model. We conclude that mental toughness should be considered as an umbrella term to represent a range of related constructs that provide a psychological advantage in performance and promote positive mental health. We also identify the limitations in existing measurement of mental toughness, and propose necessary future directions.